God and the Evolving Universe : The Next Step in Personal Evolution - Redfield, James ; Murphy, Michael, 1930 September 3- and Timbers, Sylvia, 1955- (New York Jeremy P. Tarcher/Putnam, 2002)
Unites personal and planetary evolution in order to explain how each act of individual improvement is part of a new evolutionary scheme, discussing how to discover one's place in the evolution process and promote spiritual development.
Include Index
Keywords: Cosmology -- Evolution -- Teleology